Financial Auditing and Surveys: how are financial auditors using information technology? An approach using Expert Interviews - Pedrosa, I.; Costa, C. (ISDOC '12 Proceedings of the International Conference on Information Systems and Design of Communication, 2012)
For many years, studies on Models for Individual Information Technology Acceptance were carried out and many approaches were released. All these models were meant to advance and define the determinant contributions on the user agreement on Information System and how this value can be a determinant factor to Information System adoption and success. The acceptance of Computer Assisted Audit Tools and Techniques is referred as difficult among internal auditors. This problem can arises when available tools and procedures involve relevant and complex background in several topics as Mathematics, Statistic and Advanced Concepts and Techniques on Information Systems. ANOVA or Data Mining algorithms and Artificial Intelligence on auditing procedures are examples of these evidences. This study intends to fully understand the way financial auditors use Information Technologies in their Auditing Tasks. To accomplish this main objective we did in-depth interviews focused upon financial auditors group. Is our intention to analyze and classify their contributions in order to provide further insights to the present research.